Tetradecanoic Acids With Anti-Virulence Properties Increase the Pathogenicity of Pseudomonas aeruginosa in a Murine Cutaneous Infection Model - Juárez-Rodríguez, Martha María; Cortes-López, Humberto; García-Contreras, Rodolfo; González-Pedrajo, Bertha; Díaz-Guerrero, Miguel; Martínez-Vázquez, Mariano; Rivera-Chávez, José Alberto; Soto-Hernández, Ramón Marcos; Castillo-Juárez, Israel (Frontiers in Cellular and Infection Microbiology, 2021)
Blocking virulence is a promising alternative to counteract Pseudomonas aeruginosa infections. In this regard, the phenomenon of cell-cell communication by quorum sensing (QS) is an important anti-virulence target. In this field, fatty acids (FA) have gained notoriety for their role as autoinducers, as well as anti-virulence molecules in vitro, like some saturated FA (SAFA). In this study we analyzed the anti-virulence activity of SAFA: C12-18 and compared their effect with the putative autoinducer cis-2-decenoic acid (CDA). The effect of SAFA on six QS-regulated virulence factors and on the secretion of the exoenzyme ExoU was evaluated. In addition, a murine cutaneous infection model was used to determine their influence on the establishment and damage caused by P. aeruginosa PA14. Dodecanoic (lauric, C12:0) and tetradecanoic (myristic, C14:0) acids reduced the production of pyocyanin by 25-65 % with 40 to 1000 concentration, while CDA inhibited it 71 % at 3 µM. Moreover, they reduced swarming by 90 % without affecting biofilm formation. In contrast, CDA reduced the biofilm by 57 % at 3 µM but did not affect swarming. Furthermore, SAFA: C12-18 inhibited ExoU secretion, of which lauric acid completely abolished it at 100 µM, and CDA did so at 50 µM. Remarkably, the coadministration of lauric (1000 µM) or myristic (200 and 1000 µM) acids with PA14 induced greater damage and reduced survival of the animals up to 50 %, whereas CDA (500 µM) prevented damage without affecting the viability of PA14. Hence, our results show that SAFA and CDA have a role in regulation of P. aeruginosa virulence, although their inhibition/activation molecular mechanisms are different in complex environments such as in vivo systems.